Pengaruh Rasio Likuiditas, Solvabilitas, Dan Rentabilitas Terhadap Return Saham Pada Perusahaan LQ45 Yang Terdaftar Di BEI Periode 2014-2018 - Avina Putri Adam; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to analyze 1) Does the liquidity ratio affect stock returns on LQ45 companies listed on the Indonesia Stock Exchange Period 2014-2018, 2) does the solvency ratio affect the stock returns on LQ45 companies listed on the Indonesia Stock Exchange 2014-2018 Period, 3) Does the profitability ratio affect the company in returning shares to LQ45 companies listed on the Indonesia Stock Exchange. Causality design was used in this study. Secondary data used by the author is sourced from financial statement data, publication date, LQ45 companies listed on the Indonesia Stock Exchange in the 2014-2018 period were obtained from the website www.idx.co.id. Based on the results of the study found Liquidity ratios have no effect on Return, Solvency Ratios have no effect on Stock Returns, Profitability Ratios have no effect on Stock Returns and together Liquidity Ratios, Solvency Ratios and Profitability Ratios have a significant effect On Stock Returns.